Potential asthma biomarkers identified by nontargeted proteomics of extracellular vesicles in exhaled breath condensate - Reina Hara, MD; Yoshito Takeda, MD, PhD; Takatoshi Enomoto, MD; Hanako Yoshimura, MD, PhD; Makoto Yamamoto, MD; Satoshi Tanizaki, MD; Yuya Shirai, MD, PhD; Takahiro Kawasaki, MD, PhD; Mana Nakayama; Saori Amiya, MD; Yuichi Adachi, MD; Yoshimi Noda, MD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD) are often misdiagnosed or undiagnosed, highlighting the need for more noninvasive and accessible diagnostic tools. Although exhaled breath condensate (EBC) is recognized as a biomarker resource for respiratory diseases, nontargeted proteomics of extracellular vesicles (EVs) in EBC has not been explored. Objective: Our aim was to identify protein signatures in EBC-derived EVs (EBC-EVs) and potential biomarkers for BA and COPD. Methods: EBC-EVs were isolated from 8 patients with BA, 5 patients with COPD, and 9 healthy controls by using the phosphatidylserine affinity method. The isolated EBC-EVs were analyzed by using data-independent acquisition proteomics to identify differentially expressed proteins (DEPs) and their associations with clinical parameters. Results: Overall, 2524 proteins were identified. In the patients with BA, 20 proteins were upregulated, and 34 were downregulated. In the patients with COPD, 46 proteins were upregulated and 67 were downregulated. Although the enriched pathways and protein networks showed similarities between BA and COPD, they also indicated distinct pathophysiologic differences. In all, 5 BA-DEPs and 2 COPD-DEPs correlated with clinical parameters. For BA, S100 calcium-binding protein P levels were inversely correlated with FEV1 value, and ribosomal protein S10 levels were inversely correlated with blood eosinophil count. Clathrin heavy chain 2 correlated with serum IgE levels. For COPD, 14-3-3 protein theta and galectin-related protein showed positive and negative correlations with FEV1 value, respectively. Conclusions: Proteomics of EBC-EVs has enabled the identification of potential diagnostic biomarkers for BA and COPD. “Breathomics” of EBC-EVs offers a promising noninvasive approach for diagnosis and phenotyping of respiratory diseases.